The Positive Effects of Currency Hedging Derivatives for Firm Valuation : Evidence from the Finnish Public Market 2019 - 2023 - Rintala, Niklas (My University, 2024)
The study examines the effects of using currency derivatives on publicly listed companies' valuation. In an increasingly globalizing world, it is relatively uncommon not to address any of the risks affected by the fluctuation of the changing exchange rates. Even if the firm operates only within the one domestic country and is not directly exposed to currency exchange rate movements, the risk of changing rates may come in multiple different ways. The most common way of this is through different steps in the supply chain, such as raw materials. However, international competitors can also benefit from the exchange rate fluctuations in the form of favorable changes, affecting the competitiveness of the domestic counterparty. In a perfect world with a fully functioning financial market, such a thing as hedging would not have any positive or negative effects on valuation. In a perfect world, every shareholder would be able to hedge their own financial risks leaving no need for additional risk management done by the company itself. However, the imperfectness in the global financial markets created by such things as taxes, transaction costs, and information asymmetry provide a high incentive for corporate hedging activities. Nowadays, there are multiple ways of hedging companies' business activities, making it more predictable. This has led to a situation where almost all the major companies have separate risk management departments focusing on making the best possible strategies, one of which is using currency derivatives. This study focuses on the hypothesis that using currency derivatives as a risk management tool positively affects company valuation. We will be focusing on Finnish publicly listed companies, excluding firms in the financial sector. The data will be gathered from 160 different companies from the timespan from 2019 to 2023. The main goal is to have a better understanding of the actual effects in the Finnish market. The findings will help better understand the effects of currency derivatives on risk exposure and the predictability of future cash flows. This information will be useful not only for the internal shareholders but also for investors, policymakers, and regulators to have a better understanding of the real-life effects for future decision-making.

Tutkimuksessa tarkastellaan valuuttajohdannaisten käytön vaikutuksia julkisesti noteerattujen yritysten arvostukseen. Yhä globalisoituvassa maailmassa on suhteellisen harvinaista, että muuttuvien valuuttakurssien vaihtelun aiheuttamaa riskiä ei haluttaisi minimoida. Vaikka yritys toimisi vain kotimaan markkinassa eikä suoraan altistuisi valuuttakurssimuutoksille, valuuttakurssien muutosten aiheuttama riski voi kuittenkin realisoitua monin eri tavoin. Yleisin tapa on toimitusketjun eri vaiheiden, kuten raaka-aineiden, hinnanvaihtelu. Toinen merkittävä riski on kansainvälinen kilpailu, sillä kansainväliset kilpailijat voivat hyötyä suotuisista valuuttakurssivaihteluista, mikä vaikuttaa heikentävästi kotimaisen vastapuolen kilpailukykyyn. Täydellisessä maailmassa, jossa rahoitusmarkkinat toimisivat tehokkaasti, tällaisella suojautumisella ei olisi positiivisia tai negatiivisia vaikutuksia arvostukseen. Täydellisessä maailmassa jokainen osakkeenomistaja voisi suojautua omilta rahoitusriskeiltään, jolloin ei olisi tarvetta yrityksen kokonaisvaltaiseen valuuttariskienhallintaan. Maailmanlaajuisten rahoitusmarkkinoiden epätäydellisyys, jossa suurina tekijöinä ovat muun muassa verot, transaktiokustannukset ja informaation epäsymmetriasta, kannustaa kuitenkin voimakkaasti yrityksiä toteuttamaan suojautumistoimia. Nykyään on olemassa useita tapoja suojautua yritysten liiketoiminnan riskeiltä tehden tulevaisuudesta huomattavasti ennakoitavampaa. Tämä on taas johtanut tilanteeseen, jossa lähes jokaisella suurella yrityksellä on erilliset riskienhallintaosastot, jotka keskittyvät parhaiden mahdollisten suojausstrategioiden laatimiseen. Tutkimuksessa keskitytään hypoteesiin, jonka mukaan valuuttajohdannaisten käyttäminen valuuttariskin hallintavälineenä vaikuttaa myönteisesti yrityksen arvostukseen. Keskitymme suomalaisiin julkisesti noteerattuihin yhtiöihin, pois lukien rahoitusalan yritykset. Aineisto kerätään 160 eri yritykseltä aikaväliltä 2019–2023. Päätavoitteena on saada kattavampi käsitys valuuttajohdannaisten todellisista vaikutuksista Suomen markkinoilla. Tulokset auttavat ymmärtämään paremmin valuuttajohdannaisten vaikutuksia yhtiöiden kantamaan riskiin ja tulevien kassavirtojen ennustettavuuteen. Tämä tieto on hyödyllistä paitsi yritysten sisäisille sidosryhmille, mutta myös sijoittajille, poliittisille päättäjille ja sääntelyviranomaisille, jotta he ymmärtäisivät paremmin todelliset vaikutukset tulevaa päätöksentekoa ajatellen.
Keywords: risk management; currency; derivative markets; futures; hedges; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance